Mayor Greg Goodnight : crisis in the U.S. auto industry - Bates, Lisa Tepper (SAGE knowledge. Cases., 2016)
In December 2008, the Mayor of Kokomo, Indiana - Greg Goodnight - received the news that congressional leaders had failed to agree on terms for emergency federal financial assistance for the U.S. 'Big Three' automakers. Without some sort of substantial government intervention, at least one of the three - General Motors - seemed headed for almost certain and fairly immediate bankruptcy and possible cessation of operations. Mayor Goodnight's concern was that nearly one quarter of the Kokomo area's workforce was employed directly by the auto industry. This study examines his response to the crisis.